2022
DOI: 10.3389/fnut.2022.836115
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Plasma Fatty Acid Patterns During Pregnancy With Gestational Diabetes Mellitus

Abstract: BackgroundLimited studies have explored the difference of fatty acid profile between women with and without gestational diabetes mellitus (GDM), and the results were inconsistent. Individual fatty acids tend to be interrelated because of the shared food sources and metabolic pathways. Thus, whether fatty acid patters during pregnancy were related to GDM odds needs further exploration.ObjectiveTo identify plasma fatty acid patters during pregnancy and their associations with odds of GDM.MethodsA hospital-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…As a result, it is probable that altered fatty acids in GDM women are due to impaired transfer of fatty acids via the placenta to the cord blood and fetus. 46 A study by Chen et al has reported a positive association of DHA with HOMA-IR at 15.8 weeks of gestation in 1368 pregnant women (81 GDM and 1287 controls). 47 Earlier randomised controlled trials have also been unable to show any impact of omega-3 PUFA consumption on the prevalence of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is probable that altered fatty acids in GDM women are due to impaired transfer of fatty acids via the placenta to the cord blood and fetus. 46 A study by Chen et al has reported a positive association of DHA with HOMA-IR at 15.8 weeks of gestation in 1368 pregnant women (81 GDM and 1287 controls). 47 Earlier randomised controlled trials have also been unable to show any impact of omega-3 PUFA consumption on the prevalence of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, C16:0 represents the most abundant SFAs in the human body, which can be obtained directly from dietary sources or synthesized through metabolic conversions involving other FAs, carbohydrates, and amino acids. 59,60 Under normal physiological conditions, tissue levels of C16:0 remain relatively stable due to the regulatory role of endogenous synthesis in maintaining balance even when dietary intake fluctuates. 60 However, specific physiological conditions or chronic nutritional imbalances can significantly impact de novo lipid synthesis and consequently alter the level of C16:0.…”
Section: Paper Food and Functionmentioning
confidence: 99%